Kemampuan komunikasi matematis siswa smp pada materi segiempat - Aldi Hidayatuloh; Tina Sri Sumartini (Jurnal Inovasi Pembelajaran Matematika: PowerMathEdu, 2022)
Communication skills need to be possessed by students in learning mathematics. This study aims to analyze junior high school students regarding mathematical communication skills in the quadrilateral material. This research method is descriptive qualitative. Determination of research subjects was carried out by purposive sampling by selecting 2 students of class VII. Data were obtained by conducting written tests and interviews. Each data or information obtained was analyzed in descriptive form. Learning difficulties experienced by students were analyzed based on the results of interviews. Students' mathematical communication skills were analyzed based on indicators of mathematical communication skills. The results of this study are the five indicators of students' mathematical communication skills need to be improved because they are not optimal. Factors that affect mathematical communication skills are the learning process, student understanding and the habit of giving practice questions. Kemampuan komunikasi perlu dimiliki oleh siswa dalam pembelajaran matematika. Penelitian ini bertujuan untuk menganalisis siswa SMP mengenai kemampuan komunikasi matematis pada materi Segiempat. Metode penelitian ini adalah deskriptif kualitatif. Penentuan subjek penelitian dilakukan secara Purposive Sampling dengan memilih 2 orang siswa kelas VII. Data diperoleh dengan cara melakukan tes tertulis dan wawancara. Setiap data atau informasi yang diperoleh dianalisis dalam bentuk deskriptif. Kesulitan belajar yang dialami siswa dianalisis berdasarkan hasil wawancara. Kemampuan komunikasi matematis yang dimiliki siswa dianalisis berdasarkan indikator-indikator kemampuan komunikasi matematis. Hasil penelitian ini adalah kelima indikator kemampuan komunikasi matematis siswa perlu ditingkatkan karena belum optimal. Faktor-faktor yang mempengaruhi kemampuan komunukasi matematis yaitu proses pembelajaran, pemahaman siswa serta pembiasaan pemberian latihan soal.